Haemato-Biochemical Changes During Post-Partum Cervico-Vaginal Prolapse And Its Management In A Non Descript Heifer - Talukdar, D. J.; Ahmed, K.; Talukdar, Papori; Buragohain, R. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Prolapse of genital organs is an emergence condition which adversely affects overall performance of the affected animal. It should be treated before excessive edema, traumatic lacerations fatal hemorrhage and bacterial contamination lead to unfavourable prognosis (Beheshti et al., 2011). Vaginal prolapse has been registered in delivered buffaloes, cows and sheep and usually observed in the last months of pregnancy (Noakes et al. 2000). During the last trimester of pregnancy increasing levels of oestrogen causes relaxation of the pelvic ligaments along with oedema of the vulva (Hudson, 1986). When the animal sits down the intra- abdominal pressure (especially in late pregnancy) is transmitted to the flaccid pelvic structures tending to force the relaxed and loosely attached vaginal floor and walls through the vulva, thereby favouring cervico-vaginal prolapse. Estrogens also have a suppressing effect on blood calcium causing greater relaxation of pelvic ligaments leading to genital prolapse (Richardson et al. 1981).